-6 3/5*4 2/3-10 7/9*(-6 3/5)=

0 голосов
52 просмотров

-6 3/5*4 2/3-10 7/9*(-6 3/5)=


Математика (66 баллов) | 52 просмотров
Дано ответов: 2
0 голосов

Ответ:

Пошаговое объяснение:

=-6 3/5*(4 2/3-10 7/9)=-6 3/5(4 6/9-

10 8/9=-6 3/2*(-6 2/9)=-15/2*(-56/9)=

140/3=46 2/3

(122k баллов)
0

спасибо☺

0

Пожалуйста

0 голосов

Ответ:

Пошаговое объяснение:

=-6 3/5*(4 2/3-10 7/9)=-6 3/5(4 6/9-

10 8/9=-6 3/2*(-6 2/9)=-15/2*(-56/9)=

140/3=46 2/3

(122k баллов)
0

а почему 10 8/9 ,а не 10 7/9?

0

если к общему знаменателю 9,то в скобках будет (4 6/9-10 7/10) или я не прав?

0

10 7/9